STUDY OF PERSPECTIVE BASIL VARIETIES AS SOURCES IN SELECTION ON PRODUCTIVITY AND PRECOCITY IN THE CONDITIONS OF SOUTH RUSSIA - L. N. Novikova; B. N. Novikov (Овощи России, 2019)
Few vegetable plants are a source of necessary biologically active substances. Special significance is given to spicy cultures, the most common among which is basil gardening (Ocimum basilicum L.). Its plants, possessing a rich and diverse chemical composition, are used in the medical and food industry, fresh and as components of spice mixtures to improve the quality of food. However, the basil culture is not widely spread and its use is limited. To increase the demand and consumption of this vegetable crop, the creation of promising varieties that meet modern market requirements is relevant. At the same time, it is necessary to search for sources of economically valuable traits - productivity, precocity and yield. The aim of the study was to study the collection variety samples of basil and the selection of sources of valuable features for use in breeding work. The initial material served as 72 samples of this culture of various ecological and geographical origin from the VIR collection. In the phase of mass flowering, they differ as early flowering, medium flowering and late flowering. In the phase of ripening seeds – early ripening, mid-ripening and late ripening. Selected sources of valuable features are recommended as a starting material for the selection of garden basil (Ocimum basilicum L.).